Social work in extremis : lessons for social work internationally - Lavalette, Michael; Ioakimidis, Vasilios (Bristol, U.K. ; Portland, OR : Policy Press, 2011)
This important book looks at social work responses in different countries to extreme social, economic and political situations including war situations, military regimes, earthquakes and tsunamis.
Title from publisher's bibliographic system (viewed on 01 Sep 2022).
Keywords: Social service; Disaster relief